2017
DOI: 10.3122/jabfm.2017.06.170137
|View full text |Cite
|
Sign up to set email alerts
|

Worsening Rural-Urban Gap in Hospital Mortality

Abstract: Background: One out of every 5 Americans live in rural communities. Rural Americans have higher rates of early and preventable deaths outside of the hospital than their urban counterparts. How rurality relates to hospital mortality is unknown. We sought to determine the association between rural versus urban residence and hospital mortality.Methods: This is a retrospective observational study of 4,412,942 nonmaternal, nonneonatal hospitalizations in 2008, and 3899,464 nonmaternal, nonneonatal hospitalizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Our findings are consistent with prior studies demonstrating a relationship between rurality and mortality, 1,2,4,5 though to our knowledge this is the first to look specifically at the uninsured population in recent years. One prior 2008 study looked at rural and urban differences in uninsured hospitalizations and found that uninsured patients in rural hospitals were more likely to be admitted for preventable conditions 17 ; however, that study did not look at differences in mortality nor at how these patterns were changing over time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with prior studies demonstrating a relationship between rurality and mortality, 1,2,4,5 though to our knowledge this is the first to look specifically at the uninsured population in recent years. One prior 2008 study looked at rural and urban differences in uninsured hospitalizations and found that uninsured patients in rural hospitals were more likely to be admitted for preventable conditions 17 ; however, that study did not look at differences in mortality nor at how these patterns were changing over time.…”
Section: Discussionsupporting
confidence: 92%
“…Rurality and a lack of insurance have independently been linked to worse clinical outcomes 1‐5,14 . However, little is known about how insurance status contributes to urban‐rural in‐hospital mortality disparities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For trauma patients, this may have contributed to a widening of the gap in morbidity and mortality outcomes between urban and rural populations. 38,39 Many rural patients simply cannot be delivered to an urban trauma center in a timely manner. Similarly, without an ability to offer local cesarean delivery capability, rural maternity care is largely unsustainable.…”
Section: Challenges To Providing Anesthesia and Surgical Care In Ruramentioning
confidence: 99%
“…The new single Graduate Medical Education accreditation system for both allopathic and osteopathic physicians, along with the rapid expansion of osteopathic medical schools will change the future of the US family medicine workforce. So, more doctors, but not necessarily better access to care for rural AmericansVillapiano et al 19 report on the concurrently growing urban-rural gap for hospital mortality.…”
Section: National Data With Implications For Future Health Carementioning
confidence: 99%